PERAN PENGETAHUAN WAJIB PAJAK KENDARAAN BERMOTOR (PKB) DALAM MENINGKATKAN KEPATUHAN WAJIB PAJAK DAN INTEGRITAS SISTEM PEMUNGUTAN PAJAK PADA KANTOR SAMSAT HANDIL BAKTI UNIT PELAYANAN PENDAPATAN DAERAH(UPPD)2023-2024 - Sarifah Fatimah; Lili Safrida (JRUP: JURNAL REFERENSI DAN ULASAN PERPAJAKAN, 2025)
This study discusses Motor Vehicle Tax (PKB), which is one of the factors that supports Regional Original Income (PAD), especially in Barito Kuala Regency. Although the number of vehicles continues to increase over time, this has not been in line with an increase in public compliance in paying taxes. This study aims to analyze the increase in taxpayer knowledge regarding compliance in paying PKB, as well as to evaluate how the integrity of the collection system impacts public trust. In this study, which applies a qualitative descriptive approach, data was obtained through interviews, observations, and document collection techniques. The results of this study indicate that increased taxpayer knowledge is directly proportional to increased taxpayer compliance. In addition, a collection system with integrity has also been proven to be able to build and strengthen public trust in collection institutions. Therefore, it is important to expand socialization activities and strengthen technology-based services as an effort to improve tax compliance.